Higher education teachers’ experiences of becoming research active: striving for university status in the Global South - Jeyaraj, Joanna Joseph; Wald, Navé; Harland, Tony (Springer, 2021)
Higher education institutions are seen as pivotal for fostering national economic growth in a globalised knowledge economy. Conducting research is an important aspect of that role, and there is pressure on institutions to increase their knowledge production, as well as to ofer advanced research degrees. This requires academics with doctoral level qualifcation who research in their feld. Research productivity is important for institutions because it contributes to prestige and better rankings in league tables, which result in more or better resources. This qualitative study examines the notion of ‘turning teachers into academics’ through the experiences of lecturers in a teaching-focused institution in Malaysia seeking university status. Becoming research active requires resources and a supportive environment that were largely unavailable, and so participants experienced an unhealthy intensifcation of their academic work and struggled to do research or complete their PhD qualifcations. The study showed that a successful transition required teachers to be genuinely motivated to do research and the institutions to provide adequate support. Under current circumstances of ferce competition between institutions and the inability to compromise teaching allocations, it is not clear how, or if, such a transition can happen without adversely afecting staf wellbeing.